A new Masdevallia (Orchidaceae: Pleurothallidinae) from Colombia - Doucette, Alfonso (Phytotaxa, 2012)
Masdevallia unguentum is described and illustrated for the first time from material cultivated at Finca Dracula, Panama. The morphological similarities of the species are discussed, and the species is distinguished by fragrance and unique sepal morphology.